A collection, transcription and analysis of the traditional Jakwara songs of the Karanga people in Dorset area of Somabhula - Mutambasere, Admire (Midlands State University, 2018)
The purpose of this study was to make a collection, transcription and analysis of the traditional Jakwara songs of the Karanga people in Dorset area of Somabhula.The research was made up of ten respondents. The snowball sampling technique was used in which the adult community members and village heads participated this research. A total of ten respondents constituted the sample of this research. Ethnography was the research design used to effectively collect data in this research. Qualitative methods were used and the data was collected using interviews and observations. Most respondents highlighted that Jakwara songs are important in the society for social cohesion, promoting unity and togetherness, cautioning wrong doers, giving rhythm at the threshing floor, entertainment and communication. The study concluded that Jakwara songs are gradually becoming unpopular in Dorset area mainly due to lack of documentation of the songs, Christianity, modernity, drought, Western influence. The researcher recommends that the National Arts Council of Zimbabwe and adult community members can significantly contribute towards the preservation of Jakwara songs both in schools and in the society to prevent the song from dying.